2005
DOI: 10.1007/s00216-005-3205-5
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle assemblies supported on glassy-carbon electrodes for the electro-analytical detection of hydrogen peroxide

Abstract: Electrochemical detection of hydrogen peroxide using an edge-plane pyrolytic-graphite electrode (EPPG), a glassy carbon (GC) electrode, and a silver nanoparticle-modified GC electrode is reported. It is shown, in phosphate buffer (0.05 mol L(-1), pH 7.4), that hydrogen peroxide cannot be detected directly on either the EPPG or GC electrodes. However, reduction can be facilitated by modification of the glassy-carbon surface with nanosized silver assemblies. The optimum conditions for modification of the GC elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
210
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(213 citation statements)
references
References 91 publications
2
210
0
1
Order By: Relevance
“…However, in detecting H2O2 carbon materials as such do not typically perform as well as noble metals, for instance Au and Pt [9]. It has been shown that pure glassy carbon does not catalyze redox reactions of H2O2 but by modifying the electrode surface for example with Ag [10]- [12], Pd [13], [14], Pt [15] or carbon nanotubes [16] can result in measurable electrochemical reactions. In addition, Hrapovic et al [15] demonstrated with their glassy carbon and carbon nanotube sensors that the detection limit for H2O2 with Ptdoped sensors strongly depends on the type of the carbon support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in detecting H2O2 carbon materials as such do not typically perform as well as noble metals, for instance Au and Pt [9]. It has been shown that pure glassy carbon does not catalyze redox reactions of H2O2 but by modifying the electrode surface for example with Ag [10]- [12], Pd [13], [14], Pt [15] or carbon nanotubes [16] can result in measurable electrochemical reactions. In addition, Hrapovic et al [15] demonstrated with their glassy carbon and carbon nanotube sensors that the detection limit for H2O2 with Ptdoped sensors strongly depends on the type of the carbon support.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the detection of H2O2 on conventional metal or carbon fiber electrodes is hindered by slow kinetics [10], [20] and relatively high overpotential [21], which allows also the oxidation of interfering species, such as ascorbic acid and uric acid [10]. Thus, new materials that facilitate fast and interference-free detection of H2O2 as well as resist biofouling are in demand.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical effect of the Ag nanoparticles on the GF is discussed. We chose silver nanoparticles (as model electro-active nanoparticles) due to the fact that they possess a very high surface area to volume ratio, and have been shown to exhibit electrochemical properties that make them suitable for potential application in electrochemical devices such as sensors [29][30][31] and in fuel cells (i.e. hydrogen-evolution reaction [32] and oxygen-reduction reaction [33]).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, reducing electrochemically H 2 O 2 at low working potentials (usually around 0 V versus Ag/AgCl) [5], where interfering substances are electrochemically inert, allows for a much more selective assay of the analyte. In respect to studies on the surface modified with micro-and nanostructures carbonaceous electrodes as efficient electrocatalysts of hydrogen peroxide, both oxidation and reduction [6][7][8][9][10][11][12][13] are currently on high demand.…”
Section: Introductionmentioning
confidence: 99%